Social Response in Poland in 1944–1948 - Brenk, Mikołaj (Biuletyn Historii Wychowania, 2018)
The article concerns the field of social care and social assistance in the first years of the Polish People’s Republic as they were provided to individuals who suffered distress during World War Two. The timeline of the paper covers the period from 1944 to 1948. At that time, the focus of social care and social assistance was satisfying the fundamental needs of the people, in particular in environments affected by the destruction of war. It included, among others, ensuring food, health care, accommodation, education and employment. The scale of the relief provided after the war by various Polish and international institutions was unprecedented in the history of the Polish social service, covering one in four Poles, i.e. over 6 million people in total.